Socio economic importance of connecting cross-border regions - Medeiros, E. (Boosting Cross-Border Regions through Better Transport, 2019)
Gains of effectiveness and competitiveness of public transport Economic: Less fuel consumption, less car congestion Environmental: Less atmospheric pollutant emissions Social: Enlarge offer to lower income classes - If there is a big enough population and adequate public transport services, relevant urban policy will realize the compact city that reduces environmental deterioration and improves the efficiency of people’s activities. - However, financial sustainability of public transport totally depends on population density